34. DESCRIPTION OF HEALTH INSURANCE COVERAGE RATE IN THANH SON DISTRICT, PHU THO PROVINCE IN THE PERIOD 2020-2022 (Vietnam Journal of Community Medicine, 2024)
Research objectives: This study aims to describe the health insurance coverage in Thanh Son district, Phu Tho province in the period 2020-2022. Research methods: Correlation research using secondary data and descriptive and comparative statistical methods. Research results: Thanh Son district’s social insurance has implemented many measures to increase health insurance coverage, but the ratio of doctors/10,000 people only reaches 7.2 doctors; The rate of people’s out-of-pocket spending on health reached 43% and the rate of health insurance coverage only reached 90% (imqualified the plan assigned by the Government in 2022). Conclusions: Increasing health insurance coverage in a mountainous district like Thanh Son, Phu Tho in the period 2020-2022 has encountered many difficulties (there are 6 communes that are not supported by the state budget to buy health insurance cards and 10 communes are no longer eligible to be issued free health insurance cards and the impact of the Covid-19 epidemic). Thus, there needs to be solutions to increase the rate of health insurance coverage in Thanh Son district in the coming time.
Keywords: Health insurance, health insurance coverage, Thanh Son district, Phu Tho province.